Sleep Electroencephalographic Response to Respiratory Events in Patients With Moderate Sleep Apnea–Hypopnea Syndrome - Zhou, Guolin; Pan, Yu; Yang, Juan; Zhang, Xiangmin; Guo, Xinwen; Luo, Yuxi (Frontiers in Neuroscience, 2020)
Sleep apnea/hypopnea syndrome is a common breathing disorder that can lead to organic brain injury, prevent memory consolidation, and cause other adverse mental-related complications. Brain activity while sleeping during respiratory events is related to these dysfunctions. In this study, we analyzed variations in electroencephalography (EEG) signals before, during, and after such events. Absolute and relative power as well as symbolic transfer entropy (STE) of scalp EEG signals were calculated to unveil the activity of brain regions and information interactions between them, respectively. During the respiratory events, only low-frequency power increased during rapid eye movement (REM) stage (δ-band absolute and relative power) and N1 (δ- and θ-band absolute power, δ-band relative power) sleep. But absolute power increased in low- and medium-frequency bands (δ, θ, α, and σ bands), and relative power increased mainly in the medium-frequency band (α and σ bands) during stage N2 sleep. After the respiratory events, absolute power increased in all frequency bands and sleep stages, but relative power increased in medium and high frequencies. Regarding information interactions, the β-band STE decreased during and after events. In the γ band, the intra-hemispheric STE increased during events and decreased afterwards. Moreover, the inter-hemisphere STE increased after events during REM and stage N1 sleep. The EEG changes throughout respiratory events are supporting evidences for previous EEG knowledge of the impact of sleep apnea on the brain. These findings may provide insights into the influence of the sleep apnea/hypopnea syndrome on cognitive function and neuropsychiatric defects.